: № 113 (2246) (1984)
Титульного листа нет, описание составлено по обложке Для служебного пользования, экз. № 76 Экземпляры: УКП (20240921) / Инвентарный номер: АП19840200 / Сис.шифр: 65.31 / Авт.знак: И 93 / ГРНТИ: 06.35.33 / ББК: 65.31-05